A new method for eliminating blur caused by the rotational motion of the images - Sanipour, Seyed Mohammad Ali; Ahadi Akhlaghi, Iman (PeerJ PrePrints, 2015)
The aim of this investigation is to evaluate a new method for blur elimination caused by rotational motion of any object, assuming that the center and the angle of the rotation are known. In this new method, which is called Enhanced Rotational De-convolution Conjugate Gradient (ERD-CG), first we enhanced the RD method for the blurred images, and then we combined the ERD method with the CG method (which is the reconstruction of iterative method). The experimental results are promising and show that the proposed method outperforms both RD and CG, significantly.
Keywords: Radial blurring; Image restoration; Image deblurring; Motion blur